VALUASI BAHAN GALIAN GOLONGAN C (BGGC) DI KABUPATEN CIREBON DITINJAU DARI PENGELOLAAN DAN INVESTASI - Sulaksana, Nana (Bulletin of Scientific Contribution, 2006)
In order to optimize the ability of mineral resources which are utilized to give people a more prosperous life, we need not only an adequate mining management which is appropriate with the characteristic of the mineral resources but also a stocktaking of the existence of the mineral resources in a form of map information which is included in a work identification and a mapping of mineral potencies. Exploiting the mineral resources optimally by maximizing added values and minimizing negative impacts of mineral resources exploitation, will increase the PAD (Original Local income) and labour absorption. Therefore, research continuity is essential to create in order to collect the basic information of the mineral potencies, especially constructive and industrial deposits, hopefully it will be able to support the exploitation activity. Work identification and mapping of a mineral potency represents the most basic need now, considering that Cirebon Regency has to be ready to implement the Local Autonomy based on the constitution number 22 Year 1999st, especially in a mining field. The result of the work identification will become a basic and main force for the Mining and Energy Department in Cirebon Regency in order to promote its natural resources and to accelerate duties on mine workings building and supervision.